Nazi Concentration Camp Commandants 1933-1945 : Rare Photographs from Wartime Archives - Baxter, Ian (Images of War, 2014)
Using many rare and unpublished images this book identifies and delves into the characters of the notorious men who were instrumental in one of the greatest crimes against humanity in World history.  Through words and pictures the chilling truth emerges. In many respects these monsters were all too normal. Rudolf Hess, the Commandant of Auschwitz, was a family man and hospitable host and yet while there is no record of his committing acts of violence personally he presided over a regime that accounted for over a million deaths. Others such as Amon Goeth and Josef Kramer personally promoted vio